2017
DOI: 10.1088/1748-605x/aa8dde
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electrospun polycaprolactone scaffold morphology on human kidney epithelial cells

Abstract: There is a pressing need for further advancement in tissue engineering of functional organs with a view to providing a more clinically relevant model for drug development and reduce the dependence on organ donation. Polymer based scaffolds, such as polycaprolactone (PCL), have been highlighted as a potential avenue for tissue engineered kidneys, but there is little investigation down this stream.Focus within kidney tissue engineering has been on 2-dimensional cell culture and decellularised tissue. Electrospun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 81 publications
(97 reference statements)
0
57
1
Order By: Relevance
“…4. Although, our results regarding fibre diameter and its influence on cell behaviour are not conclusive, it has been shown to have major implication in previous studies [39,[56][57][58]. There is some disparity between our data for CellTitre blue and DNA quantification, this is possibly as a result of the much greater porosity gained from cryogenic electrospinning where unattached cells become trapped within the scaffold.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…4. Although, our results regarding fibre diameter and its influence on cell behaviour are not conclusive, it has been shown to have major implication in previous studies [39,[56][57][58]. There is some disparity between our data for CellTitre blue and DNA quantification, this is possibly as a result of the much greater porosity gained from cryogenic electrospinning where unattached cells become trapped within the scaffold.…”
Section: Discussioncontrasting
confidence: 68%
“…Our work follows on from the limited published research into the use of kidney cells with electrospun scaffolds [13,30,55]. We have previously shown that electrospun PCL can be used to grow a kidney cells line, and highlighted the effects of morphological differences in scaffolds [39]. Here we have gone further, using RPK cells and demonstrating the survival of key cell types of this multi-cell population, Fig.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…PCL/ECM scaffolds were electrospun using the following parameters: 0.4 mm needle bore, 0.8 mL/hr volume flow rate (6 mL in total), 12 cm mandrel: needle distance, +14 kV positive charge, −4 kV negative charge, and 250 revolutions per minute mandrel rotational speed. These parameters have been shown to create uniform randomly aligned small fibers of PCL (Burton et al, ). The mandrel was coated with aluminum foil for collection.…”
Section: Methodsmentioning
confidence: 99%
“…Materials used in vascular tissue engineering include decellularized extracellular matrices, biopolymers, bioabsorbable polymers, and collagen (Gilbert, Sellaro, & Badylak, ; Hong et al, ; Hutmacher, ; Jiang et al, ; Lu, Lin, Kim, et al, ; Masoumi et al, ; Reid & Callanan, ; Wu, Liu, Cui, Qu, & Chen, ). Electrospinning is a widely used technique that mimics the nanoscale and microscale structure of tissues and has been utilized in a large number of tissue engineering avenues for various organs (Burton & Callanan, ; Burton, Corcoran, & Callanan, ; Dettin et al, ; Gao et al, ; Garrigues, Little, Sanches‐Adams, et al, ; Grant, Hay, & Callanan, ; Han, Gerstenhaber, Lazarovici, & Lelkes, ; Hong et al, ; Kumbar, Nukavarapu, James, Nair, & Laurencin, ; Masoumi et al, ; Sundaramurthi, Krishnan, & Sethuraman, ). Furthermore, while polymers can control architecture, they lack some of the unique biomolecular cues found in native tissue, which is why, in recent years, there has been an increase in demand for decellularized ECM (Kasimir et al, ; Sanchez, Fernandez‐Santos, Costanza, et al, ; Tapias & Ott, ; Weymann, Patil, Sabashnikov, et al, ).…”
Section: Introductionmentioning
confidence: 99%